PIFA-Mediated Synthesis of Acylsulfenic Acid Alkyl Esters and Benzoyl Alkyl Disulfides from Thioacids - Tsai, Chia-Hsuan; Reddy, Daggula Mallikarjuna; Hsieh, Ping-An; Liu, Yi-Chen; Kandasamy, Mohanraj; Lin, Wei-Yu; Lee, Chin-Fa (Synthesis, 2016)
A simple and convenient approach for the synthesis of acylsulfenic acid alkyl esters and benzoyl alkyl disulfides from thiobenzoic acids is described. This reaction uses commercially available [bis(trifluoroacetoxy)iodo]benzene (PIFA) as an oxidant under mild reaction conditions.
Keywords: thioacids; alcohols; thiols; oxidations; PIFA; acylsulfenic acid alkyl esters; disulfides